Marx and Whitehead : process, dialectics, and the critique of capitalism - Pomeroy, Anne Fairchild (SUNY series in the philosophy of the social sciences., 2004)
Marx and Whitehead boldly asks us to reconsider capitalism, not merely as an "economic system" but as a fundamentally self-destructive mode that, by its very nature and operation, undermines the cohesive fabric of human existence. Author Anne Fairchild Pomeroy asserts that it is impossible to appreciate fully the impact of Marx's critique of capitalism without understanding the philosophical system that underlies it. Alfred North Whitehead's work is used to forge a systematic link between process philosophy and dialectical materialism via the category of production. Whitehead's process thought brings Marx's philosophical vision into sharper focus. This union provides the grounds for Pomeroy's claim that the heart of Marx's critique of capitalism is fundamentally ontological, and that therefore the necessary condition for genuine human flourishing lies in overcoming the capitalist form of social relations